Marketing network and pesticide use in the district of Tandil, a sector in the southeast of the province of Buenos Aires, Argentina (Huellas, 2021)
Agricultural activity is an engine of the Argentine economy, and given the extensive use of pesticides in food production, it is essential to understand their handling to assess their effects on the environment and people's health. The objective was to know the main aspects of the network of actors that use and commercialize pesticides in the Tandil district (Buenos Aires) during 2019 and 2020. Qualified referents were interviewed and agricultural producers in the area were surveyed. 10 main actors were identified, grouped into 3 categories (government agencies, civil and private associations) which proved to be linked through activities such as control, training or trade flows. The key actors agreed on the scarcity of resources assigned to control, the low use of the agronomic recipe and the diverse final destination of the empty drums. Added to this, the anthropocentric look in relation to nature, the lack of professional advice in the fields, and distrust in agroecological production is evident. The need to incorporate new actors into the network, generate public policies that allow greater control, and the urgency of undergoing a change in the productive paradigm is concluded.
Keywords: network of actors; agro-industrial production model; lack of control; lack of advice; management of public policies; change of production paradigm; healthy food